Factor XIII of Blood Coagulation as a Nuclear Crosslinking Enzyme - Ádány, Róza; Bárdos, Helga; Antal, Miklós; Módis, László; Sárváry, Attila; Szücs, Sándor; Balogh, Imre (Thrombosis and Haemostasis, 2001)
Intracellular localization and distribution of Factor XIII subunit A (FXIIIA) was investigated in association with monocyte-macrophage differentiation in a long term culture of human monocytes by light-and electron microscopical as well as biochemical and immunobio-chemical techniques. To allow the detection of FXIIIA in cells with well-preserved ultrustructure, immunosera against glutaraldehydederivatized recombinant FXIIIA were developed in rabbits, then characterized and used in this study. In the early phase of macrophage differentiation intranuclear accumulation of FXIIIA was detected as a transient phenomenon in cells of the 2nd day culture by optical sectioning with 0,7 m steps in laser scanning confocal microscopy and immunoblotting technique. FXIIIA could be detected by immuno-electron microscopic postembedding staining over electrodense DNA-containing areas. Fluoresceinated monodansylcadaverine incorporation assay was used to demonstrate that FXIIIA is not only present in the nuclei, but also expresses its transglutaminase activity. Our finding of the nuclear accumulation of FXIIIA in differentiating human macrophages is also unique in that a blood clotting factor has, for the first time, been localized in nuclei and has been shown to be an intracellular crosslinking enzyme. The possible role of nuclear FXIIIA in association with cellular processes involving chromatin structure remodeling, such as cell death, cell differentiation or cellular proliferation requires further in-depth investigation.
Keywords: Factor XIII; transglutaminase; cell-nucleus; monocyte-macrophage differentiation; confocal microscopy